Object detection using geometric invariant moment - Mohamed Rizon; Haniza, Yazid; Puteh, Saad; Ali Yeon, Md Shakaff, Prof. Dr.; Abdul Rahman, Saad; Mohd Rozailan, Mamat; Sazali, Yaacob, Prof. Dr.; Hazri, Desa, Dr.; Karthigayan, M. (Science Publications, 2011)
Link to publisher's homepage at http://www.scipub.org/